Kebijakan Amerika Serikat Menyetujui Perjanjian Perdamaian dengan Taliban dan Penarikan Pasukan Amerika Serikat dari Afghanistan di Masa Kepemimpinan Donald Trump - Safna Putri Purba; Reni Windiani; Satwika Paramasatya (Journal of International Relations, 2022)
The war between the United States and the Taliban has entered two decades. The US eventually dispatched representatives to negotiate with the Taliban. President Donald Trump has also directed that his troops leave Afghan territory at regular intervals. The negotiation process between the US and the Taliban was tense, but an agreement was eventually reached. Both parties signed the peace agreement in Doha, Qatar, on February 29, 2020. As such, why did the United States, under President Donald Trump's leadership, reach a peace agreement with the Taliban and withdraw American troops from Afghanistan? The purpose of this study is to explain his study employs explanatory research and neoclassical realism theory to identify the factors that influence foreign policy. The result of this study is that the United States' policy to make peace with the Taliban and withdrawal from Afghanistan is the influence of NATO and explains by domestic influence the perception of Trump towards the conflict in Afghanistan.